Relations between self-efficacy beliefs, self-presentation motives, personal task goals, and performance on endurance-based physical activity tasks. (January 2016) - Howle, Timothy C.; Dimmock, James A.; Jackson, Ben
Abstract: We conducted two studies with the aim of examining the relations between self-presentation motives and physical activity task performance. In study 1, prior to performing an endurance-based physical activity task, 133 undergraduate participants ( M age  = 20.89, SD  = 5.21) reported acquisitive-agentic and protective-agentic self-presentation motives alongside task self-efficacy, self-presentational efficacy, and their personal task goals. Using a different endurance-based physical activity task in study 2, we also assessed undergraduate participants' ( n  = 150; M age  = 20.23, SD  = 3.34) dispositional exercise-related self-presentation motivation alongside the variables measured in study 1. Bayesian path analyses revealed indirect relations between agentic self-presentation motives and task performance via participants' personal task goals. Findings also indicated that agentic self-presentation motives may act as intermediaries in indirect pathways linking efficacy beliefs and dispositional exercise-related self-presentation motivation to goal processes and task performance. The results contribute to a more nuanced understanding of the relationship between self-presentation motivation and task performance. Highlights: Situational and dispositional self-presentation motives were considered. Bayesian analysis helped account for theory and previous research findings. There were indirect pathways from agentic self-presentation motives to task performance. Agentic motives also supported indirect effects from other constructs to performance.